Polimosfismo genético da glicose-6-fosfato desidrogenase na população da região de Araraquara-SP - Ferreira, Rosecler Inácia de Paula [UNESP]; Leite, Fábio Renato Manzolli; Leite, Amauri Antiquera [UNESP] (My University, 2014)
The most important role played by the enzyme Glucose- 6-Phosphate Dehydrogenase (G6PD) in erythrocyte metabolism is in generating energy and reducing power used to protect the cell against oxidative attack. G6PD deficiency is the erythroenzymopathy that most frequently causes hemolytic anemia, and more than 130 molecular variants have already been identified. The aim of this study was to analyze the genetic mutations in the G6PD-deficient adult males in the population of the region of Araraquara, São Paulo State. Out of 5087 male blood donors, 89 were deficient for G6PD, as confirmed by assaying the enzyme activity and electrophoresis on cellulose acetate. Thus, a frequency of 1.75% of G6PD-deficient patients was found, this value being similar to other investigations in São Paulo state. Molecular analysis was performed by amplification of genomic DNA with specific primers and digestion with restriction enzymes. In 96.6% of the patients, the G6PD A¯ variant was observed, with mutations at residues 376(A→G) and 202(G→A). Mean G6PD specific activity among the patients was 1.31 IU.g Hb-1.min-1 at 37ºC, that is 10.8% of the normal activity of the G6PD B enzyme. The variant forms G6PD A¯ 680(G→T) and 968(T→C) were not found. In 3.4% of the deficient individuals, the G6PD Mediterranean variant was found, with a mutation at 563(C→T). In these cases, mean enzymatic activity was 0.25 IU.g Hb-1.min-1 at 37ºC, or 2.1% of the enzymatic activity of G6PD B. The use of traditional techniques, allied to the identification of the different molecular variants, is important for the understanding of the structural and functional properties and hemolytic behavior of the red blood cells of the patient.

A importância da enzima Glicose-6-fosfato desidrogenase (G6PD) no metabolismo eritrocitário está na obtenção de energia calórica e redutora para a proteção celular contra agressões oxidativas. A deficiência de G6PD é a eritroenzimopatia que causa mais frequentemente anemia hemolítica, com mais de 130 variantes moleculares identificadas. O objetivo deste estudo foi realizar a análise molecular da deficiência de G6PD em uma população masculina adulta da região de Araraquara, SP, para a identificação das mutações genéticas. Nos 5087 doadores de sangue do sexo masculino pesquisados, foram encontrados 89 deficientes de G6PD, confirmados pela determinação da atividade enzimática e eletroforese em acetato de celulose, com frequência de 1,75%, valores semelhantes aos encontrados por outros pesquisadores no Estado de São Paulo. A análise molecular realizada pela amplificação do DNA genômico com iniciadores específicos e digestão com enzimas de restrição, demonstrou que 96,6% dos deficientes apresentaram a variante G6PD A¯, com as mutações 376(A→G) e 202(G→A) e atividade enzimática média de 1,31 UI.g de Hb-1.min-1 a 37º C, correspondendo a 10,8% da atividade enzimática da enzima normal G6PD B. Não foram encontradas as formas variantes G6PD A¯ 680(G→T) e 968(T→C). Em 3,4% dos indivíduos deficientes, foi encontrada a variante G6PD Mediterrânea, mutação 563(C→T) e atividade enzimática média de 0,25 UI.g de Hb-1.min-1 a 37ºC, correspondendo a 2,1% da atividade enzimática da G6PD B. A utilização das técnicas tradicionais, aliadas à identificação da variante molecular, são importantes na compreensão das propriedades estruturais, funcionais e comportamento hemolítico dos glóbulos vermelhos do paciente.
Genetic polymorphism of glucose-6-phosphate dehydrogenase in the population of Araraquara, State of São Paulo
Keywords: Glucosephosphate dehydrogenase deficiency; Molecular biology; Genetic polymorphism; Deficiência de G6PD; Biologia molecular; Polimorfismo genético